Pengembangan Sumber Daya Manusia Dalam Bidang Administrasi - Sewanto, Alfando Digo; Ikram, Muhammad Davin; Ramadhan, Zidane Haydar; Azmi, Salasatina Hasna Muti; Fauzi, Hendayani Risti; Purwandari, Rochma; Shella, Shyfa Dwi Nur; Saputri, Jelita Hermanda Dwi; Rezzabadi, Muhammad Fai; Kurniawan, Arif; Muhammad, Danang Wahyu (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Human resource (HR) development in administration is a crucial factor in improving the quality of public services in Padukuhan Mandungan I, Margoluwih Village. This study aims to analyze efforts to develop HR in the administrative sector. A descriptive qualitative method was used, with data collected through interviews, observations, and documentation with community leaders, village officials, and health workers. The results show that development is carried out through training involving 23 participants and the implementation of a technology-based administration system called SIPADU. The web-based system has recorded 317 individual data entries and 78 households, supported by training for 5 RT-level admins. The main challenges faced are limited budgets and a lack of skilled personnel. Collaboration between government, the community, and educational institutions is needed to sustain the program. HR development is expected to foster a more orderly administrative environment and improve public service efficiency